The Effect of Using Artificial Intelligence And Illustrated Text on Students’ Reading Comprehension of Narrative Text - Irmayana, Aprida; Pasaribu, Abigail Stevany; Insani, Nur; Silitonga, Novita Sriwahyuni; Panggabean, Hana Oktavia (International Journal of English and Applied Linguistics (IJEAL), 2026)
The aim of this study is to know the difference of using and without using illustrated text on students’ reading comprehension of narrative text at the eighth grade students of SMP Negeri 1 Sipirok, to know the extent of teaching reading of narrative text by applying and without applying illustrated text at the eighth grade students of SMP Negeri 1 Sipirok, to know the extent the students’ reading comprehension of narrative text by using and without using illustrated text, to find out whether there is any significant differences of students’ reading comprehension of narrative text by using ilustrated text and without using illustrated text at the eighth grade students of SMP Negeri 1 Sipirok. The method that used in this research was quantitative method. The design of this research was quasi-experimental design. The population of this research at the eighth grade students of SMP Negeri1Sipirok consists of 158 students. The researcher uses purposive sampling technique to get the sample that VIII-1 and VIII-2 that both consists of 32 students. The data was obtained by distributing observation sheet and also test. The researcher found that the results of the used of Illustrated Text in students’ reading comprehension of narrative text at the eighth grade students of SMP Negeri 1 Sipirok in 2025/2026 academic year is more than 85.7% and categorized “very good”. The score of students’ reading comprehension of narrative text without using illustrated text was 53,91 and categorized “bad” and the students’ reading comprehension of narrative text by using illustrated text was 73.44% and categorized “good”. There is any significant difference of students reading comprehension of narrative text by using illustrated text than without using illustrated text at the eighth grade students of SMP Negeri 1 Sipirok in 2025/2026 academic year that significant was less than 0,05 (this research significant was 0.00) and the null hypothesis is rejected, and the alternative hypothesis is accepted.